PELATIHAN TEACHING ENGLISH TO YOUNG LEARNER UNTUK GURU DI PAUD AL HIKMAH DESA GEDUNG RAJA - Pamungkas, Arimbi; Tri Dewantari; Maya Oktavia (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem that arises in learning English for early childhood is the teacher's understanding of using appropriate media and methods in the process of learning English for early childhood at PAUD Al Hikmah, Gedung Raja Village, Abung Pekurun District, North Lampung Regency. This community service activity was carried out with the aim of providing Teaching English to Young Learner training for Al Hikmah PAUD teachers, Gedung Raja village, Abung Pekurun District, North Lampung Regency. This activity aims to provide teachers with insight and knowledge about how to teach English for early childhood. The method used in this activity is the lecture and discussion method. The steps for this activity are preparation, implementation, and evaluation. After the three stages have been completed, it can be concluded that using appropriate media and methods in learning English can make it easier for teachers to introduce English to young children. The results of community service carried out face to face went smoothly and well.